Check GMAT Club Decision Tracker for the Latest School Decision Releases https://gmatclub.com/AppTrack

 It is currently 26 May 2017, 17:20

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# What is the value of y + x^3 + x? (1) y = x (x - 3) (x + 3)

Author Message
Current Student
Joined: 29 Jan 2005
Posts: 5221
Followers: 26

Kudos [?]: 403 [0], given: 0

What is the value of y + x^3 + x? (1) y = x (x - 3) (x + 3) [#permalink]

### Show Tags

25 Mar 2006, 21:11
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 0 sessions

### HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

What is the value of y + x^3 + x?

(1) y = x (x - 3) (x + 3)

(2) y = -5x
SVP
Joined: 24 Sep 2005
Posts: 1885
Followers: 22

Kudos [?]: 323 [0], given: 0

### Show Tags

25 Mar 2006, 21:20
GMATT73 wrote:
What is the value of S= y + x^3 + x?

(1) y = x (x - 3) (x + 3)

(2) y = -5x

(1) y= x( x^2-9) = x^3 - 9x
--> S= x^3- 9x + x^3 +x= 2*x^3 - 8x --> can't point out the concrete value of S -->insuff

(2) y= -5x --> S= x^3 - 4x --> insuff

(1) and (2):

we have y= x(x-3) ( x+3) = -5x --> x^3 - 9x = -5x --> x^3 - 4x= 0
from 2 we have: S= x^3 - 4x --> S= 0 --> suff

C it is.
Current Student
Joined: 29 Jan 2005
Posts: 5221
Followers: 26

Kudos [?]: 403 [0], given: 0

### Show Tags

25 Mar 2006, 21:54
laxieqv wrote:
GMATT73 wrote:
What is the value of S= y + x^3 + x?

(1) y = x (x - 3) (x + 3)

(2) y = -5x

(1) y= x( x^2-9) = x^3 - 9x
--> S= x^3- 9x + x^3 +x= 2*x^3 - 8x --> can't point out the concrete value of S -->insuff

(2) y= -5x --> S= x^3 - 4x --> insuff

(1) and (2):

we have y= x(x-3) ( x+3) = -5x --> x^3 - 9x = -5x --> x^3 - 4x= 0
from 2 we have: S= x^3 - 4x --> S= 0 --> suff

C it is.

Duh Laxie, your explanation makes spotting the trick seem so effortless. YOU RULE!
SVP
Joined: 14 Dec 2004
Posts: 1692
Followers: 3

Kudos [?]: 145 [0], given: 0

### Show Tags

25 Mar 2006, 22:24
"C" it is!

using both we get x^3-4x = 0, which is given equation too!
Manager
Joined: 20 Nov 2004
Posts: 108
Followers: 0

Kudos [?]: 3 [0], given: 0

### Show Tags

26 Mar 2006, 11:07
laxieqv wrote:
S= x^3 - 4x --> S= 0 --> suff

C it is.

Well that's not sufficient, since x^3 - 4x has 3 roots
at -2, 0, and +2. The graph looks like the Z of Zorro

So it is E.
Attachments

File comment: Graph of x^3 - 4x

Z.jpg [ 12.93 KiB | Viewed 603 times ]

SVP
Joined: 24 Sep 2005
Posts: 1885
Followers: 22

Kudos [?]: 323 [0], given: 0

### Show Tags

26 Mar 2006, 11:14
ccax wrote:
laxieqv wrote:
S= x^3 - 4x --> S= 0 --> suff

C it is.

Well that's not sufficient, since x^3 - 4x has 3 roots
at -2, 0, and +2. The graph looks like the Z of Zorro

So it is E.

But we don't need to consider the roots here

We only care about the value of the whole expression ( x^3- 4x) which has the value of 0
Manager
Joined: 20 Nov 2004
Posts: 108
Followers: 0

Kudos [?]: 3 [0], given: 0

### Show Tags

26 Mar 2006, 11:20
laxieqv wrote:
We only care about the value of the whole expression ( x^3- 4x) which has the value of 0

Ok, ok, I admit it is C.
VP
Joined: 29 Apr 2003
Posts: 1403
Followers: 2

Kudos [?]: 29 [0], given: 0

### Show Tags

01 Apr 2006, 06:08
Its C.

I like the way u used graphs 2 solve... GMAT shud have some graph questions!
01 Apr 2006, 06:08
Display posts from previous: Sort by